AN INVESTIGATION INTO THE MECHANISM OF ELASTASE INHIBITION BY CEPHALOSPORINS USING ELECTROSPRAY-IONIZATION MASS-SPECTROMETRY - Aplin, R; Robinson, C; Schofield, C; Westwood, N (1993)
Electrospray ionisation mass spectrometry was used to investigate the mechanism of inhibition of porcine pancreatic elastase (PPE) by two cephalosporins, L-658758 [1-[[3-(acetoxymethyl)-7α-metyoxy-8-oxo-5-thia-1-azabicyclo[4.2.0.]oct-2-en-2-yl]carbonyl]proline S,S dioxide], and L-647957 [1-[[3-(acetoxymethyl)-7α-chloro-8-oxo-5-thia-1-azabicyclo[4.2.0]oct-2-en-2-yl]carboxylic tbutyl ester]S,S dioxide]. The mass shifts, observed as compared with native PPE, upon incubation with the inhibitors were consistent with the formation of an acyl enzyme complex followed by expulsion of the acetoxy group from the 3′-methylene position of the cephalosporin inhibitors. In the case of L-647957 the mass shifts also indicated loss of HCl. In contrast for L-658758, no evidence was accrued for loss of methanol, consistent with previous kinetic studies on human leukocyte elastase. © 1993.